Kemampuan Membaca Memahami Dongeng Berbahasa Jerman “Frau Holle” - Sridevisari Sridevisari; Wahyu Kurniati Asri (Phonologie : Journal of Language and Literature, 2023)
Abstract. This study aims to determine the ability to read and understand the German fairy tale "Frau Holle" of Class XII students at SMAN 8 Makassar and the factors that influence the ability to read and understand German fairy tales for class XII students at SMAN 8 Makassar. This study uses a quantitative descriptive method. Data collection using written tests and questionnaires. Data analysis using percentage technique. The population in this study were students of class XII IPA 1, XII IPA 2 and XII IPA 3 at SMAN 8 Makassar. The sample in this study were 32 students of class XII IPA 3 at SMAN 8 Makassar. The results of this study indicate that the ability to read and understand the German fairy tale “Frau Holle” for class XII students at SMAN 8 Makassar is in the very good category (87.5%). There are two factors that influence the ability to read and understand the German-language fairy tale "Frau Holle", namely the supporting factors that come from within the students themselves and from the availability of German books at school and the inhibiting factors in the form of the attitude of intelligence of students who think that German language is difficult and external factors, namely the school environment.Keyword: Ability, Reading, Understanding, German Fairy Tales